2010
DOI: 10.1128/jb.01308-09
|View full text |Cite
|
Sign up to set email alerts
|

Expression of Factor H Binding Protein of Meningococcus Responds to Oxygen Limitation through a Dedicated FNR-Regulated Promoter

Abstract: Factor H binding protein (fHBP) is a surface-exposed lipoprotein in Neisseria meningitidis, which is a component of several investigational vaccines against serogroup B meningococcus (MenB) currently in development. fHBP enables the bacterium to evade complement-mediated killing by binding factor H, a key downregulator of the complement alternative pathway, and, in addition, fHBP is important for meningococcal survival in the presence of the antimicrobial peptide LL-37. In this study, we investigate the molecu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
65
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 35 publications
(71 citation statements)
references
References 54 publications
6
65
0
Order By: Relevance
“…Increasing amounts of IPTG (Sigma)-0, 0.0075, 0.03, and 0.1 mM-were added to the initial culture medium to modulate the expression of fHbp. Immunoblotting and FACS analyses were performed using anti-fHbp var1.1 polyclonal antisera, as previously described (7,33).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Increasing amounts of IPTG (Sigma)-0, 0.0075, 0.03, and 0.1 mM-were added to the initial culture medium to modulate the expression of fHbp. Immunoblotting and FACS analyses were performed using anti-fHbp var1.1 polyclonal antisera, as previously described (7,33).…”
Section: Methodsmentioning
confidence: 99%
“…Upstream of the fHbp gene and similarly oriented is the cbbA gene encoding a fructose-bisphosphate aldolase. Previous studies have shown that the fHbp gene is transcribed from a FNR-regulated promoter, responsible for oxygen-dependent regulation of fHbp, within the upstream intergenic region and at least in some strains is also transcribed in a bicistronic transcript with the cbbA gene (7).…”
mentioning
confidence: 99%
“…first fHbp-overexpressing strain was prepared by transforming the recombinant ⌬LpxL1 strain with the suicide plasmid pComPindFnrD148A (32), which generated the recombinant strain ⌬LpxL1-FNR c . This strain contained the mutant activator of fHbp expression, FNR-D148A, under the control of the IPTG (isopropyl-␤-D-thiogalactopyranoside)-inducible P tac promoter, which was integrated into the chromosome.…”
mentioning
confidence: 99%
“…In addition to MnB, other serogroups (A, C, W135, X, and Y) have been shown to contain fHBP (36,38). The recent finding that fHBP gene transcription is expressed from two separate promoters, which are regulated by both oxygen and iron availability, further suggests the important role of fHBP in the virulence and pathogenesis of N. meningitidis (91). Although some sequence variation is exhibited by fHBP (32), the protein still maintains conserved regions for binding human fH and reactivity to protective immune sera.…”
Section: Resultsmentioning
confidence: 98%
“…Although free iron concentrations in the bloodstream are low, N. meningitidis has access to iron through iron binding proteins such as transferrin, lactoferrin, and hemoglobin. Oriente et al demonstrated that fHBP expression is under the control of two independent promoters: a bicistronic transcript originating from an upstream gene and a monocistronic transcript from the promoter of fHBP, P fHBP (91). P fHBP contains a putative FNR box motif such that under oxygen limitation, transcription is upregulated from P fHBP in an FNR-dependent manner.…”
Section: Regulation Of Fhbp Expressionmentioning
confidence: 99%